Root coverage using modified tunneling technique with acellular dermal matrix for treatment of gingival recession associated with orthodontic treatment: A case report - Rosa Pratiwi; Irma Dewi Ratnawati; Agung Krismariono (Odonto : Dental Journal, 2023)
Background: Gingival recession has a number of causes, including orthodontic therapy. The degree and extent of gingival recession and orthodontic therapy are strongly correlated. Care must be taken in choosing the best soft tissue grafting technique. Development of a number of new and improved surgical techniques, including the modified tunneling technique. Case Management: A-24-year-old female patient came to Periodontic Clinic Dental Hospital of Airlangga University with a chief complain of gingival recession in mandibular central incisors since 6 months ago. The patient complained about dental sensitivity. The dental history revealed that she had undergone fixed orthodontic therapy for 7 years. She revealed the fixed orthodontic appliance was put off since 8 months ago. The patient concern about her appearance and aesthetic problem. Gingival recession on buccal surface tooth 31 and 41 extending 1,5-2 mm apical of the incisors was found in clinical assessment. This case classified as Miller class III. The doctor planned root coverage procedure using modified tunnel technique. Acellular dermal matrix (SuredermÂ®) was chosen as a gingival graft. Discussion: Creating a "tunnel" through the buccal mucosa to treat gingival recession enables coronal repositioning of the soft tissue with predictable root coverage and a pleasing appearance. Tissue graft implantation is made possible by a horizontal incision. Conclusion: In brief, root coverage using modified tunnel technique is effective and predictable treatment modality. Comparing with other root coverage method it give quite satisfying result. The use of Acellular Dermal Matrix (ADM) considered as an alternative to Connective Tissue Graft (CTG).